Chimerism of Carbon by Ruthenium Induces Gradient Catalysis. (18th June 2021) - Sun, Zhuang; Yang, Chushu; Jiang, Fangling; Zhang, Tao
Abstract: Improving the round‐trip efficiency and cycle life of lithium‐oxygen batteries (LOBs) through the cathode design is essential for their employment in electric vehicles. Here, a neoteric chimeric air‐cathode is proposed, in which ultra‐dispersed ruthenium (Ru) nanoparticles are partially confined by microtube walls of free‐standing carbon textiles, but petty parts of Ru with catalytic surfaces are exposed. The special chimeric structure benefits not only for preventing nanocatalysts agglomeration but also tailoring the formation/decomposition mechanisms of lithium peroxide (Li2 O2 ) during oxygen reduction/evolution reactions. Critically, theoretical simulations disclose that the enlarged chimeric catalyst‐support interphase between the Ru and carbon matrix enhances the electron density of Ru particles and then induces a gradient Gibbs free energy of LiO2 adsorption energy at active sites, and thus fundamentally modulates the morphology evolution mechanism of finial Li2 O2 . In the LOBs, the chimeric electrode affords a remarkably high energy efficiency of 84.1% and long‐term cyclability (260 cycles at 300 mA g −1 ). Abstract : Totally different from the traditional catalysts anchored on the support, chimerism of carbon by catalysts benefits not only preventing nanocatalyst agglomeration but also enhancing charge transfer between the "carbon‐donor" and "ruthenium‐acceptor" by enlarging the contact interface, inducing a gradient catalytic performances at the chimeric ruthenium active phases.